Secondary prevention medications after coronary artery bypass grafting and long-term survival: a population-based longitudinal study from the SWEDEHEART registry. (22nd October 2019) - Björklund, Erik; Nielsen, Susanne J; Hansson, Emma C; Karlsson, Martin; Wallinder, Andreas; Martinsson, Andreas; Tygesen, Hans; Romlin, Birgitta S; Malm, Carl Johan; Pivodic, Aldina; Jeppsson, Anders
Abstract: Aims: To evaluate the long-term use of secondary prevention medications [statins, β-blockers, renin–angiotensin–aldosterone system (RAAS) inhibitors, and platelet inhibitors] after coronary artery bypass grafting (CABG) and the association between medication use and mortality. Methods and results: All patients who underwent isolated CABG in Sweden from 2006 to 2015 and survived at least 6 months after discharge were included ( n  = 28 812). Individual patient data from SWEDEHEART and other mandatory nationwide registries were merged. Multivariable Cox regression models using time-updated data on dispensed prescriptions were used to assess associations between medication use and long-term mortality. Statins were dispensed to 93.9% of the patients 6 months after discharge and to 77.3% 8 years later. Corresponding figures for β-blockers were 91.0% and 76.4%, for RAAS inhibitors 72.9% and 65.9%, and for platelet inhibitors 93.0% and 79.8%. All medications were dispensed less often to patients ≥75 years. Treatment with statins [hazard ratio (HR) 0.56, 95% confidence interval (95% CI) 0.52–0.60], RAAS inhibitors (HR 0.78, 95% CI 0.73–0.84), and platelet inhibitors (HR 0.74, 95% CI 0.69–0.81) were individually associated with lower mortality risk after adjustment for age, gender, comorbidities, and use of other secondary preventive drugs (all P  < 0.001). There was no association between β-blockers and mortality risk (HR 0.97, 95% CI 0.90–1.06; P  = 0.54). Conclusion: The use of secondary prevention medications after CABG was high early after surgery but decreased significantly over time. The results of this observational study, with inherent risk of selection bias, suggest that treatment with statins, RAAS inhibitors, and platelet inhibitors is essential after CABG whereas the routine use of β-blockers may be questioned.